2016
DOI: 10.1108/mrr-03-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

Challenging corporate commitment to CSR

Abstract: Purpose In times of crisis, the fundamental principles of companies erode, leading to strategy shifts. This paper aims to examine whether corporate social responsibility (CSR) is on management’s agenda in times of crisis, indicating CSR embeddedness into corporate strategy. The focus is on the four pillars of CSR: social, environment, economy and governance. Design/methodology/approach Starting points are competing hypotheses based on shareholder and stakeholder theory. Chief executive officer (CEO) letters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…By doing so, participation in CSR related activities can only be possible when managers have higher emotional attachment and feelings of obligations towards CSR activites. Developing of CSR orientation and CSR competencies are not sufficient for the execution of CSR functions, but also required commitment to CSR related activities (Fehre & Weber, 2016). Second, this study suggests that CSR orientation and CSR competencies are the pre‐conditions and powerful predictor of CSR commitment.…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, participation in CSR related activities can only be possible when managers have higher emotional attachment and feelings of obligations towards CSR activites. Developing of CSR orientation and CSR competencies are not sufficient for the execution of CSR functions, but also required commitment to CSR related activities (Fehre & Weber, 2016). Second, this study suggests that CSR orientation and CSR competencies are the pre‐conditions and powerful predictor of CSR commitment.…”
Section: Discussionmentioning
confidence: 99%
“…According to public opinions, financial challenges and profit-making ability are deemed as the core aspects of a company in times of crisis. In contrast, other social challenges and responsibilities of the business are important but ignored in previous research, however, these challenges are supported by some of the previous research papers [4][5][6].…”
Section: Introductionmentioning
confidence: 95%
“…Studies indicate that changes are related to adapting to trends, especially in terms of society's expectations about firms' behaviour and the evolution of their economic performance(Tengblad & Ohlsson, 2010). For example,Fehre and Weber (2016) found that the CEOs of German-listed companies talked less about CSR, including social issues, in times of crisis. Studies on the…”
mentioning
confidence: 99%